Developing a Filiart online course for information technology college students - Fernandez, Maria Theresa C.
The study aimed to develop a FiliArt online course for Information Technology students at Asia Pacific College. The researcher presented and analyzed documents pertinent to the development of FiliArt as an online course. A course syllabus was proposed. The current FiliArt being delivered in the traditional classroom instruction has definitely the potential for an online course. It was recommended in this study that blended learning is the appropriate type of online instruction suited for the nature of FiliArt as a course in which students are still guided and the instructor as facilitator of learning. Instructors in Filipino who will be online instructors must undergo formal training in online course development and delivery.